Paradigm Shifts for Literary Translation - William Maynard Hutchins (Translation Studies: Theory and Practice)
My essay argues that there have been important paradigm shifts for the translation of Arabic literature to English during the last century from Orientalist to Civilization Studies and to Modeling, for example.